A New Combination in Deschampsia (Poaceae) in Arctic North America 1 - Chiapella, Jorge Oscar (Novon: A Journal for Botanical Nomenclature)
Northern North American populations of Deschampsia P. Beauv. (Poaceae) present many taxonomic and nomenclatural problems resulting from: 1) morphologic clinal variation across the continent; and 2) overlap in taxonomic use of specific and/or infraspecific epithets that are also used in European or Russian plants. The new name D. cespitosa (L.) P. Beauv. subsp. septentrionalis Chiapella replaces the illegitimate combination D. cespitosa subsp. brevifolia (R. Br.) Tzvelev [[ D. brevifolia R. Br.]. Fil: Chiapella, Jorge Oscar. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto Multidisciplinario de Biología Vegetal. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Instituto Multidisciplinario de Biología Vegetal; Argentina